THE EVIDENTIARY VALUE OF VISUM ET REPERTUM IN RAPE CASES AND ITS RELATION TO THE LEGALITY OF ABORTION - Elvina Azaria; Elvina Azaria; Triono Eddy; Juli Moertiono (Journal Analytica Islamica, 2025)
Rape is a serious crime that causes physical harm and deep psychological trauma to the victim. One of the main challenges in law enforcement is proof, as it often occurs without witnesses. This study aims to analyze the legal evidence of Visum et Repertum (VeR), its relation to the legality of abortion for victims, and the legal protection for doctors performing conditional abortion in Indonesia. Using a normative juridical method, the study finds that VeR is crucial as scientific evidence and an administrative requirement for conditional abortion, while also protecting victims' rights. Practical challenges include limited forensic personnel, examination costs, social stigma, and insufficient legal protection for medical practitioners. Legal uncertainties create doubts in implementing conditional abortion. The study emphasizes improving VeR quality, raising awareness of victims' rights, and strengthening legal protection for doctors to ensure justice and legal certainty.